Career Development of Generation Z Employees: The Role of Organizational Support, Performance, and Job Fit - Insan, Muhammad Yalzamul; Batubara, Soulthan Saladin (CV Raskha Media Group, 2025)
This study aims to analyze the effects of organizational support, fairness in performance appraisal systems, and person–job fit on the career development of Generation Z employees working in the micro, small, and medium enterprise (MSME) sector in Indonesia. Using a quantitative approach and path analysis, the study examines differences in perceptions based on employment status and tests a theoretical model incorporating self-efficacy and career adaptability as mediating variables. The findings indicate that both organizational and individual factors play a crucial role in shaping career attitudes and employees’ organizational attachment. These results provide strategic implications for human resource management, particularly in fostering a supportive and fair work environment to encourage proactive and sustainable career development.